Electricity demand and supply in South Africa: is nuclear energy a feasible alternative to coal for baseload energy supply in South Africa? - Maqanda, Vuyani (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Climate change mitigation has created pressure on the energy mix choices of all countries. Highly polluting energy sources are increasingly unpopular. Renewable energy options have emerged as preferred choices for the low-emissions transition. Proponents of nuclear power have promoted the technology as a low-emissions technology by focusing on the operational phase and ignoring the other polluting phases. South Africa generated about 83% of its electricity supply from coal in 2019 and was rated as the 12th most polluting country in the world. In addition to the high pollution levels, the ageing coal fleet suffered from poor maintenance that resulted in frequent power blackouts. One of the government's energy plans from 2010 proposed the addition of 9 600 MW of nuclear capacity by 2030. However, this plan was not implemented. This study investigates why nuclear power historically never expanded beyond a single power facility in South Africa as well as the possible future role of nuclear power in alleviating South Africa's current electricity supply constraints and emissions commitments in the period up to 2050. Qualitative analysis is used for this study with a focus on historical document analysis and interviews with energy experts. Two research methods, case studies, and expert opinions were used in this study with data sourced from policy documents, Statistics South Africa, the World Bank, and published articles from various platforms. The Hotelling model, focusing on the impact of price differentials on energy transitions, was used as a theoretical framework. The conclusion from applying the model was that nuclear power was more expensive than the other options even when internalisation of pollution externalities was considered and therefore nuclear power could not displace the cheaper alternatives like coal based on price factors alone. The Multi-Level Perspective, working through institutions, revealed that the institutional setting did not support a transition to nuclear energy. The lack of coordination of strategies derailed the transition. The comparative case study analysis of Germany, the UK, Australia, and India reaffirmed this as countries with better coordination succeeded in transitions. Energy experts offered differing views on the feasibility of nuclear power but many agreed that South Africa should focus on technologies it has better competencies in.
Keywords: Nuclear energy Economic aspects -- South Africa; Electric power distribution -- South Africa; Supply and demand; Coal power; Energy transition -- South Africa; Renewable energy sources -- South Africa